2022
DOI: 10.1016/j.hemonc.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The Hispanic Paradox in Non-Small Cell Lung Cancer

Abstract: Objective/Background: According to the U.S. Census Bureau, 18% of the total population in the United States identified themselves as Hispanic in 2016 making it the largest minority group. This study aimed to evaluate the effect of Hispanic ethnicity on the overall survival of patients with non-small cell lung cancer (NSCLC) using a large national cancer database. Methods: We used the National Cancer Database to identify patients diagnosed with NSCLC bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…The study found that Hispanics had significantly better overall survival (OS) rates compared with other ethnic groups, regardless of their insurance status, income, educational level, or place of residence. This observation may be attributed to physical, cultural, social, and environmental factors contributing to better survival rates and decreased incidence of lung cancer among Hispanics compared with other minorities 8 …”
Section: The Hispanic Paradoxmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that Hispanics had significantly better overall survival (OS) rates compared with other ethnic groups, regardless of their insurance status, income, educational level, or place of residence. This observation may be attributed to physical, cultural, social, and environmental factors contributing to better survival rates and decreased incidence of lung cancer among Hispanics compared with other minorities 8 …”
Section: The Hispanic Paradoxmentioning
confidence: 99%
“…Several studies have shown that Hispanics with lung cancer tend to have a better survival rate compared with Blacks, Asians, and Pacific Islanders. [5][6][7] Kumar et al 8 conducted a study involving more than 555,000 patients with non-small cell lung cancer (NSCLC) from the National Cancer Database between 2010 and 2015. The study found that Hispanics had significantly better overall survival (OS) rates compared with other ethnic groups, regardless of their insurance status, income, educational level, or place of residence.…”
Section: The Hispanic Paradoxmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lung cancer is also the leading cause of death for Hispanic men and the second most common cause of death for Hispanic women [ 1 , 3 ]. Despite a lower incidence and mortality from lung cancer as a result of earlier intervention, detection, and smoking cessation over recent years, Hispanics and Latinos comprise a large number of heterogenous subpopulations that vary from the general population due, in part, to social, demographic, and environmental factors [ 4 ]. Although Hispanics have a 25% reduced incidence and 35% reduced mortality from cancer compared to non-Hispanic whites, combined data of Hispanics/Latinos as a whole can fail to acknowledge the essential heterogeneity within various subpopulations—including variable cancer risk [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…La SG para los pacientes con alteraciones oncogénicas tratados en 1ª línea con inhibidores de tirosin-quinasa fue de 49.9 meses (IC95% 43.2-56.5), para aquellos con PD-L1 ≥50% tratados en 1ª o 2ª línea con inhibidores de PD-1 fue de 33.5 meses (IC95% 29.5-37.4), y para los que no cumplieron ninguna de estas dos condiciones fue de 17.3 meses (IC95% 16.2-18.5; P=0.0001) (Figura 3). Estos hallazgos explican la considerable transición en el diagnóstico y tratamiento del CPCNP, revelando el impacto de Una vez comprendida la paradoja del cáncer de pulmón entre los hispanos, etnia con diagnósticos más tardíos y mejor SG (29), parece relativamente sencillo asimilar la ancestría de la enfermedad. Recientemente, Carrot-Zhang y colaboradores realizaron el análisis genómico y de la ascendencia de 1.153 pacientes con CPCNP de México y Colombia, encontrando asociaciones entre la ancestría nativo-americana (NAT) y el marco de las alteraciones somáticas, incluyendo la carga mutacional (TMB) y el compromiso de EGFR, KRAS y STK11 (30).…”
unclassified